The Role of Media Digital in Building Democracy in Indonesia - Pribadi SM, Probo (Indonesia Media Law Review, 2023)
The rise of digitalization has transformed the media landscape, providing individuals with convenient, rapid, practical, and cost-effective access to diverse information and news. However, concerns have been raised about the tendency of digital media to prioritize sensationalism over factual reporting, driven by the pursuit of high ratings and clicks, often neglecting core journalistic principles. This scientific article aims to explore the concept of digital media, trace its evolution, and evaluate its role in promoting democracy. The research methodology primarily relies on an extensive literature review, incorporating a range of sources such as books, journals, articles, and relevant websites to gather comprehensive insights. The findings underscore the significant impact of digital media in shaping and reinforcing democratic systems. In the digital age, digital media empowers the public by facilitating active participation in political discussions and decision-making processes, thereby enhancing transparency and accountability within political systems.